Posição socioeconômica no curso de vida, inflamação crônica e aterosclerose subclínica no estudo longitudinal de saúde do adulto (ELSA-BRASIL) - Lidyane do Valle Camelo (2014)
The exposure to social adversity across the life course is associated with a higher burden of cardiovascular disease morbidity and mortality. However, little is known about the mechanisms that could mediate this association such as biological and behavioral mechanisms, as well as the mechanisms related to stress. The aim of this dissertation was to investigate the socioeconomic position (SEP) across the life course and its association with chronic inflammation and subclinical atherosclerosis in Brazilian context. In addition, we explored factors that could mediate this association as health-risk behaviors, metabolic alterations and job stress. As a source of information, we use data from the baseline (2008-2010) of the Brazilian Longitudinal Study of Adult Health (ELSA-Brasil). Chronic inflammation was measured by C-reactive protein (CRP). Using multiple linear regression models, we found that low childhood SEP (measured by maternal education) was associated with increased CRP. However, this association was not independent of young SEP (evaluated by participants own education) and adulthood SEP (assessed by occupational social class and by per capita household income). Nevertheless, we found that CRP increased linearly with increasing numbers of exposure to unfavorable social circumstances over the life course. Using structural equation modeling, we found that the clustering of metabolic alterations (obesity, hypertension, low HDL, hypertriglyceridemia and diabetes) accounted for 49.5% of the total effect of cumulative SEP (latent variable composed by indicators of SEP in childhood, young and adulthood) in CRP among women, but this proportion was lower among men (20.2%). The clustering of health-risk behaviors (smoking, physical inactivity and excessive alcohol consumption) accounted for 13.4% of the total effect of cumulative SEP in CRP in men, but this percentage was only 4.4% among women. Consequently, the direct effect of cumulative SEP in CRP (which was not mediated by the clustering of metabolic alterations and health-risk behaviors) was high (63.2% and 44.6% among men and women, respectively). Subclinical atherosclerosis was assessed by carotid intima-media thickness (IMT). Using multiple linear regression models, we found that low childhood SEP (measured by maternal education) was associated with higher levels of IMT only among women. Low young SEP (evaluated by participants own education) and adulthood SEP (measured by occupational social class) were associated with an increase in IMT in both genders. IMT also increased with increasing numbers of exposure to adverse social conditions throughout the life course, especially among women. We performed a directed acyclic graph (DAG) to express the causal relationships between life course SEP and IMT in order to investigate the mediating role of job stress, assessed by the Brazilian version of the Swedish Demand-Control-Support Questionnaire (DCSQ). Neither job strain, evaluated by Karasekmodel, nor low job control substantially explained the association between low life course SEP and increased IMT, since job strain and low job control were not associated with IMT independently of SEP in men, and in women the passive work and low control only slightly attenuated the association between IMT and all SEP indicators. Low life course SEP was associated with chronic inflammation and subclinical atherosclerosis in Brazilian context. These findings suggest that social interventions in a single life stage may be insufficient to deal with the health inequalities. Significant portion of the association between life course SEP and CRP was not mediated by health-risk behaviors and metabolic alterations, which suggests that other mechanisms may be involved in mediating this association, such as psychosocial stress. However, we found that job stress did not mediate the association between life course SEP and IMT. Job stress is only one aspect of psychosocial stress and other sources of stress, which were not evaluated in this dissertation, may be important in explaining the health inequalities in Brazilian context, which can be explored in the future using data of the ELSA-Brasil cohort.